Pengaruh Interaksi Sosial dengan Hasil Belajar IPS Siswa Kelas V MIN 12 Kota Medan - Hasibuan, Nurkhadizah; Yusnaldi, Eka (EduInovasi: Journal of Basic Educational Studies, 2024)
This study examines the effect of social interaction on social studies teaching results for fifth grade students at Min 12 Medan City. The definition of social interaction is the relationship that occurs from an individual to another individual, each of which can influence one another. The ability to interact is something that every student needs to have because humans are said to be social beings and require interaction. High interaction will result in teaching results on social studies material for grade 5, and the higher will be the analysis technique carried out with descriptive statistical analysis. The hypothesis is tested using collarational analysis through the formula on the moment product by utilizing Excel. . From trials conducted on 15 question items, it was found that each of these questions could be used as a questionnaire to find out the interactions that occurred between students because they had gone through validation both in the form of items and content by utilizing the formula from the moment product and testing the reliability of the instrument. One of the important things to do before taking action is to test it in the form of linearity of normality and correlation between products. The analysis is carried out using a simple linear regression analysis technique through the t test and the coefficient of determination. Through the research that has been done at MIN 12 Medan city, the regression equation is obtained with the magnitude Y = 51.592 + 0.537 X. Based on the t test, it is found that tcount = 3.480. Degrees of freedom dk = 27 and a significant level of 5%, so that the price ttable = 1.703 is obtained. Through calculations obtained tcount> ttable (3.480 > 1.703) so that towards Ho experienced rejection As for Aa experienced acceptance from this study showed the results of the influence of social interaction on students related to teaching outcomes in social studies subjects at MIN 12 Medan city on the coefficient of determination the magnitude is 0.310 with the understanding that the average student's ability to carry out social interactions contributes to the results of teaching them with a magnitude of 31.0% from the regression equation Y = 51.592 + 0.537 X The remaining 69.0% is determined by other factors. Keywords: Student, Social Interaction, Learning Outcomes, Social Science